State and nation building - Kothari,Rajni (ed.) (Bombay, 1976)
As in many earlier epochs of change, there has existed a large hiatus between objective reality and political theory in the period since 1945. This period was marked by the collapse of colonial order and the successful culmination of national revolutions in many parts of the world, in effect transforming the world political structure and ushering in an epoch as momentous as the age of the industrial revolution and the age of imperialism. Yet the dominant paradigms in political theory were preoccupied with the notions of development and modernization (conceived in terms of transforming human diversity into the monolithic image provided by Western social science). It is a commentary on the power of words in our times that the theoretical models let loose by the concepts of development and modernization succeeded for a quarter century in subverting the process of national regeneration of ex-colonial societies and rendering newly independent polities into dependent states.
Keywords: Political science